2007
DOI: 10.1172/jci28984
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRs are critical for PI3K/Akt activation and negatively regulated by mTOR

Abstract: The receptor tyrosine kinase/PI3K/Akt/mammalian target of rapamycin (RTK/PI3K/Akt/mTOR) pathway is frequently altered in tumors. Inactivating mutations of either the TSC1 or the TSC2 tumor-suppressor genes cause tuberous sclerosis complex (TSC), a benign tumor syndrome in which there is both hyperactivation of mTOR and inhibition of RTK/PI3K/Akt signaling, partially due to reduced PDGFR expression. We report here that activation of PI3K or Akt, or deletion of phosphatase and tensin homolog (PTEN) in mouse embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
300
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(322 citation statements)
references
References 49 publications
(17 reference statements)
16
300
0
2
Order By: Relevance
“…Rapamycin activated Akt and increased expression of the platelet-derived growth factor receptor in TSC-deficient cells (30). However, the mechanism does not appear to be inhibition of plateletderived growth factor receptor degradation as is the case for IRS-1, but an effect at the mRNA level.…”
Section: Discussionmentioning
confidence: 93%
“…Rapamycin activated Akt and increased expression of the platelet-derived growth factor receptor in TSC-deficient cells (30). However, the mechanism does not appear to be inhibition of plateletderived growth factor receptor degradation as is the case for IRS-1, but an effect at the mRNA level.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously shown that feedback activation of Akt signaling significantly inhibits the clinical efficacy of rapamycin (10). This appears to be mediated through S6K1 inhibition and up-regulation of receptor tyrosine kinases or their substrates (11,15), although the factors that mediate feedback activation in patients have yet to be fully elucidated. Here we asked whether expression of the most common EGFR mutant, constitutively active, ligand-independent mutant EGFRvIII (16,17) could accentuate the feedback activation of Akt in response to rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…BEX2 antibody was from Abcam (Cambridge, MA). Anti-phospho-S6 (Ser-235/236) and anti-S6 antibodies have been described previously (28), TSC2, ␤-actin, and all HRP-labeled secondary antibodies were from Santa Cruz Biotechnology (Santa Cruz, CA). STAT3, p-STAT3 (Tyr-705), p65, p-p65 (Ser-536), mTOR, Raptor, Rictor, and PTEN antibodies were from Cell Signaling Technology (Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%